Rotavirus replication is correlated with S/G2 interphase arrest of the host cell cycle. - Selene Glück; Antonino Buttafuoco; Anita F Meier; Francesca Arnoldi; Bernd Vogt; Elisabeth M Schraner; Mathias Ackermann; Catherine Eichwald (PLoS ONE)
In infected cells rotavirus (RV) replicates in viroplasms, cytosolic structures that require a stabilized microtubule (MT) network for their assembly, maintenance of the structure and perinuclear localization. Therefore, we hypothesized that RV could interfere with the MT-breakdown that takes place in mitosis during cell division. Using synchronized RV-permissive cells, we show that RV infection arrests the cell cycle in S/G2 phase, thus favoring replication by improving viroplasms formation, viral protein translation, and viral assembly. The arrest in S/G2 phase is independent of the host or viral strain and relies on active RV replication. RV infection causes cyclin B1 down-regulation, consistent with blocking entry into mitosis. With the aid of chemical inhibitors, the cytoskeleton network was linked to specific signaling pathways of the RV-induced cell cycle arrest. We found that upon RV infection Eg5 kinesin was delocalized from the pericentriolar region to the viroplasms. We used a MA104-Fucci system to identify three RV proteins (NSP3, NSP5, and VP2) involved in cell cycle arrest in the S-phase. Our data indicate that there is a strong correlation between the cell cycle arrest and RV replication.